Kaemperfol alleviates pyroptosis and microglia-mediated neuroinflammation in Parkinson's disease via inhibiting p38MAPK/NF-κB signaling pathway. (January 2022) - Cai, Meiyun; Zhuang, Wenxin; Lv, E; Liu, Zhan; Wang, Yanqiang; Zhang, Wenyi; Fu, Wenyu
Abstract: The study aims to investigate whether kaemperfol (KAE) inhibits microglia pyroptosis and subsequent neuroinflammatory response to exert neuroprotective effects, along with the underlying mechanisms. The results showed KAE could ameliorate the behavioral deficits of Parkinson's disease (PD) rats, inhibit the activation of microglia and astrocytes, reduce the loss of TH-positive neurons, down-regulate levels of pyroptosis-related NOD-like receptor family pyrin domain containing 3 (NLRP3), GasderminD-N Term (GSDMD-NT), caspase1, apoptosis-associated speck-like protein containing a caspase-recruitment domain (ASC), interleukin (IL)-1β, and IL-18, and decrease the levels of inflammatory molecules (inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2)) and p38 mitogen-activated protein kinase/nuclear factor-kappaB (p38MAPK/NF-κB) signaling pathway molecules (p38MAPK, p-p38MAPK, NF-κB, and p-NF-κB) in the substantia nigra of PD rats. Further in vitro study indicated that KAE reversed the activation of BV2 cells and down-regulated the expressions of pyrolytic proteins, inflammatory mediators and key molecules in p38MAPK/NF-κB signaling pathway. Collectively, KAE inhibits the microglia pyroptosis and subsequent neuroinflammatory response to exert neuroprotective effects on 6-hydroxydopamine (6-OHDA)-induced PD rats and lipopolysaccharide (LPS)-induced BV2 inflammatory cells through inhibiting p38MAPK/NF-κB signaling pathway. Graphical abstract: Image 1 Highlights: KAE plays a neuroprotective role in dopaminergic neuron of PD. Neuroprotective effect of KAE may be achieved by inhibiting pyroptosis of microglia. Inhibition of p38MAPK/NF-κB pathway is one of the mechanisms by which KAE exerts anti-neuroinflammatory and anti-pyrolytic effects.